Pengaruh Bantuan Benih dan Pupuk Cair terhadap Pendapatan Petani Padi di Desa Setail Kecamatan Genteng Kabupaten Banyuwangi - Khafi, Sukron; Purwadhini, Ari Septianingtyas (KUBIS, 2023)
Providing assistance with rice seeds and liquid fertilizer in Setail Village will begin in 2021. This research aims to determine income in one harvest and the differences before and after receiving assistance. The time for data collection was carried out in December 2022 for rice farmers who received seed and liquid fertilizer assistance in Setail Village, Genteng District. The location was determined based on the number of rice farmers receiving seed and liquid fertilizer assistance in Setail Village. This research uses primary and secondary data. The analytical method used is Income Analysis and Paired Samples T-Test. Based on the results of the research and discussion, it can be concluded as follows: 1. TR > TC value, so it can be said that the income from rice farming in Setail Village, Genteng District is profitable. 2. The results of the paired simple t-test analysis show that the significance value of the test is 0.000, which is smaller than the real level value, namely 0.05 or 5%, so there is a difference in income between before and after receiving seed and liquid fertilizer assistance.